Hidden Behind Autophagy: The Unconventional Roles of ATG Proteins. (30th July 2013) - Bestebroer, Jovanka; V'kovski, Philip; Mauthe, Mario; Reggiori, Fulvio
<x xml:space="preserve">Abstract</x> The transport pathway of autophagy is characterized by double‐membrane vesicles called autophagosomes, which are formed through the concerted action of the conserved ATG. Until recently it was assumed that ATG proteins were exclusively involved in autophagy. A growing number of studies, however, have revealed that specific ATG proteins have roles beyond their involvement in autophagosome biogenesis. This article reviews this fast expanding new field of the autophagy research. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>